1996
DOI: 10.1046/j.1365-2362.1996.186316.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of the Ro/SSA60KD autoantigen reveals disease‐specific antibody‐binding profiles

Abstract: Anti-Ro60KD autoantibodies are commonly found in sera from patients with primary Sjögren's syndrome (SS) and systemic lupus erythematosus (SLE). In order to identify the epitopes of this autoantigen, 22-mer, synthetic peptides overlapping by eight residues, and covering the entire sequence of the Ro60KD autoantigen were prepared. Three groups of sera were evaluated according to their autoantibody specificites. The first group consisted of monospecific anti Ro60KD sera from four patients with SLE and one with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
52
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 31 publications
(36 reference statements)
5
52
1
2
Order By: Relevance
“…SLE and SS (32)(33)(34)(35)(36)(37). Our identified dominant B cell epitopes corresponding to aa 281-315 lie within this region.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…SLE and SS (32)(33)(34)(35)(36)(37). Our identified dominant B cell epitopes corresponding to aa 281-315 lie within this region.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have variably identified B cell epitopes of hRo60 from sera of patients with SLE and SS (32)(33)(34)(35)(36)(37)(38)(39). The discrepancies probably reflect the different populations studied and the types of assays and Ags selected.…”
Section: Discussionmentioning
confidence: 98%
“…The fine B cell epitope mapping of autoantibodies to La/SSB was performed using overlapping synthetic peptides. The length of the peptides used was rather long (20 amino acids), since in previous studies of Ro60kD epitopes it was shown that long peptides exhibited higher specificity [29] compared with overlapping octapeptides [30]. In fact, the mimotope scanning of Ro60kD molecule, using 22 mer overlapping synthetic peptides, revealed two discrete, disease-specific epitopes (one associated with SS and the other with SLE), compared with 14 epitopes defined by the octapeptides.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have suggested that the separate analysis of the two Ro antibodies may be important in the differentiation of SLE from SS, as anti-Ro60 would be prevalent in patients with SLE and anti-Ro52 would be prevalent in patients with SS (3,29,32). Other studies, however, were less positive on this point, having found overlapping features between antibody specificity and the kind of disease (1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in view of reports that autoantibodies to the 52-kDa component are more frequently found in the sera of SS patients, whereas autoantibodies to the 60-kDa component are more often observed in SLE patients (3,29,32), and that this different behavior may be helpful in the differential diagnosis of these autoimmune disorders, we also evaluated the prevalence and distribution of the two anti-Ro antibodies in patients with an established diagnosis of SS or SLE.…”
mentioning
confidence: 99%